Anion-cation co-doped sodium ferric sulfate positive electrode material, preparation method thereof and application of sodium ion battery

By using anion and cation co-doping technology and spray drying in sodium ferric sulfate positive electrode materials, the problems of poor air stability and insufficient electrochemical performance of sodium ferric sulfate are solved, and the high structural stability and electrochemical performance of the material are improved, providing a highly efficient positive electrode material solution for sodium ion batteries.

CN119764406APending Publication Date: 2025-04-04NORTHWESTERN POLYTECHNICAL UNIV

Patent Information

Application Number
CN202411969889.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Sodium ferric sulfate has poor air stability and insufficient electrochemical performance.

Method used

By uniformly dispersing ferrous sulfate, manganese sulfate, sodium sulfate, sodium phosphate and conductive carbon materials in water in a certain proportion, preparing a precursor mixed solution, using spray drying method to quickly form uniform particles, and co-doping of anions and cations is completed during high-temperature sintering, an anion and cation co-doping of sodium ferrosulfate positive electrode material was prepared.

Benefits of technology

The structural stability and electronic conductivity of the sodium ferric sulfate positive electrode material are significantly improved, ensuring efficient transmission of sodium ions and electrons, improving the specific capacity, rate performance and cycle life of the material, and significantly enhancing the stability in humid environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764406A_ABST
    Figure CN119764406A_ABST
Patent Text Reader

Abstract

The invention discloses an anion-cation co-doped sodium ferric sulfate positive electrode material, a preparation method thereof and application of a sodium ion battery, and relates to the technical field of electrode materials. The method comprises the following steps: dispersing ferrous sulfate, manganese sulfate, sodium sulfate, sodium phosphate and conductive carbon in water according to a certain proportion, uniformly mixing, carrying out spray drying to obtain precursor particles, and finally sintering in an inert atmosphere at a certain temperature for several hours to obtain the anion-cation co-doped sodium ferric sulfate positive electrode material. The positive electrode material shows excellent electrochemical performance in the sodium ion battery, the electrochemical performance comprises relatively high specific capacity and long cycle life, the stability of the positive electrode material in air is remarkably improved, and the positive electrode material is suitable for long-life and large-scale energy storage application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrode materials, and in particular to an anion-cation co-doped sodium iron sulfate positive electrode material, a preparation method thereof, and application of a sodium ion battery. Background Art

[0002] As an economical alternative to lithium-ion batteries, sodium-ion batteries have shown broad application prospects in the fields of energy storage and power tools due to their abundant resources, low cost and environmental friendliness. However, the performance of cathode materials is still a key bottleneck restricting the further promotion of sodium-ion batteries. Currently, the cathode materials widely studied include layered transition metal oxides, Prussian blue analogs and polyanion compounds, among which polyanion materials have gradually become a research hotspot due to their unique structural and performance advantages.

[0003] The advantages of polyanion materials in sodium-ion batteries are mainly reflected in the following aspects: First, polyanion materials are known for their stable crystal framework structure. The framework of this type of material is composed of oxides and anionic groups (such as phosphate PO4) connected by strong covalent bonds. 3- , sulfate SO4 2- (etc.), which can effectively alleviate the change of material volume during the charge and discharge process, thereby significantly improving the cycle stability. In contrast, layered oxide materials are prone to collapse or irreversible changes in the crystal structure during the ion extraction process, resulting in a significant decrease in their lifespan. Secondly, polyanionic materials have a high redox potential due to their anion-induced effect. For example, sodium iron sulfate (Na2Fe2(SO4)3) has become a representative of polyanionic materials with its discharge platform of up to 3.8V. This high voltage characteristic not only improves the energy density of sodium-ion batteries, but also makes them more competitive in large-scale energy storage devices. In addition, the three-dimensional ion diffusion channel design of polyanionic materials makes the migration path of sodium ions in the material shorter and the diffusion kinetics better, thereby greatly improving the rate performance. In contrast, although the diffusion path of Prussian blue analogs is short, their stability in the electrolyte is poor, which limits their long-term application. In addition, polyanionic materials have a diversity of chemical compositions and flexibility in regulation. By adjusting the anionic groups (such as the introduction or combination of phosphate and sulfate), the material properties can be customized. Taking sulfate as an example, its strong inductive effect can enhance the efficiency of sodium ion transmission, while providing stronger structural stability and antioxidant properties. Compared with layered transition metal oxides, polyanionic materials are more outstanding in terms of stability, controllability and environmental adaptability. Summary of the invention

[0004] In view of the deficiencies in the above-mentioned background technology, the present invention mainly solves the problems of poor air stability and insufficient electrochemical performance of sodium ferric sulfate. The present invention provides an anion-cation co-doped sodium ferric sulfate positive electrode material, a preparation method thereof, and an application of a sodium ion battery. The method is prepared by uniformly dispersing ferrous sulfate, manganese sulfate, sodium sulfate, sodium phosphate and conductive carbon material in water in a certain proportion to prepare a precursor mixed solution, and then using a spray drying method to quickly form uniform particles, and completing the co-doping of anions and cations during high-temperature sintering. Compared with the traditional method, the process greatly improves the structural stability and electronic conductivity of the sodium ferric sulfate positive electrode material, ensures the efficient transmission of sodium ions and electrons, and is suitable for industrial production. The prepared material has a high sodium storage specific capacity, a high voltage platform, excellent cycle stability and rate performance, and significantly enhances stability in a humid environment. The method uses low-cost, easily available raw materials, combined with an environmentally friendly and efficient process flow, and is widely applicable to fields such as grid energy storage and low-speed electric vehicles, providing reliable support for the commercialization of sodium ion batteries.

[0005] The first object of the present invention is to provide a method for preparing an anion-cation co-doped sodium iron sulfate positive electrode material, comprising the following steps:

[0006] Evenly disperse ferrous sulfate, manganese sulfate, sodium sulfate, sodium phosphate and conductive carbon material in water according to a certain proportion to obtain a mixed solution.

[0007] The mixed solution is spray-dried at a certain temperature to obtain precursor particles;

[0008] In an inert atmosphere, the precursor particles are heated to a predetermined temperature and kept warm for a period of time to obtain an anion-cation co-doped sodium iron sulfate positive electrode material.

[0009] Preferably, the molar ratio of ferrous sulfate to manganese sulfate is 1:0.1-0.5; the molar ratio of the total molar amount of manganese sulfate and ferrous sulfate to sodium sulfate is 1:1.5-2.0; and the molar ratio of sodium sulfate to sodium phosphate is 1:0.05-0.2.

[0010] Preferably, the conductive carbon material is one or more of carbon nanotubes, graphene, Ketjen black, conductive graphite, and acetylene black.

[0011] Preferably, the mass percentage of the conductive carbon material is 3-15%.

[0012] Preferably, when the mixed solution is spray-dried at a certain temperature, the mixed solution is placed in a spray device, the temperature is 120-200°C, and the spraying rate during spraying is 100-300m 3 / h.

[0013] Preferably, the precursor particles are heated to a predetermined temperature and kept warm for a period of time, including: a heating rate of 0.5 to 20° C. / min, a predetermined temperature of 300 to 450° C., and a keeping time of 3 to 48 hours.

[0014] Preferably, the inert atmosphere is one or more of argon, nitrogen and helium.

[0015] The second object of the present invention is to provide an anion-cation co-doped sodium iron sulfate positive electrode material.

[0016] The third object of the present invention is to provide an application of an anion-cation co-doped sodium iron sulfate positive electrode material in a sodium ion battery.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] The present invention provides an anion-cation co-doped sodium ferric sulfate positive electrode material, a preparation method thereof, and an application of a sodium ion battery. The present invention uses ferrous sulfate and sodium sulfate as main raw materials, manganese sulfate and sodium phosphate as doping raw materials, and conductive carbon material as a composite material to develop an efficient and simple positive electrode material preparation process. The method does not require dehydration of the raw materials, nor does it require reliance on high-cost processing equipment or chemical reagents, reflecting the advantages of low cost and environmental protection. Through traditional spray drying technology, the mixed precursor solution is quickly converted into a sintered precursor with uniform particle size, effectively avoiding the problem of particle agglomeration or unevenness in the traditional preparation method. Subsequently, high-temperature sintering is performed in an inert atmosphere to complete the doping of manganese ions and phosphate ions, realize the preparation of anion-cation co-doped sodium ferric sulfate material, and significantly improve the air stability and electrochemical performance of the material. The doped anions and cations not only enhance the structural stability of the material, but also improve the transmission characteristics of sodium ions and electrons, thereby significantly improving the specific capacity, rate performance and cycle life of the electrode material. The method of the present invention is simple, safe and reliable, fully utilizes the low cost advantage of raw materials, and achieves excellent material properties through innovative processes. It is suitable for large-scale preparation and provides an efficient and feasible technical path for the development of positive electrode materials for sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is the infrared spectrum of the positive electrode material prepared in Example 1.

[0020] Figure 2 This is the Raman spectrum of the positive electrode material prepared in Example 1.

[0021] Figure 3 This is the cyclic voltammetry curve of the positive electrode material prepared in Example 1 at a scan rate of 0.6 mV / s.

[0022] Figure 4This is the charge and discharge curve of the positive electrode material prepared in Example 1 at a current density of 0.1C.

[0023] Figure 5 This is a cycle performance diagram of the positive electrode material prepared in Example 1 at a current density of 1C.

[0024] Figure 6 This is the cycling performance diagram of the positive electrode material prepared in Control Example 1 at 1C current density. DETAILED DESCRIPTION

[0025] In order to enable those skilled in the art to better understand and implement the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention.

[0026] The present invention addresses the problems of low electronic conductivity and air sensitivity of polyanionic materials in their applications. The present invention combines anion and cation doping modification technology with spray drying, which not only achieves uniform control of material particle size, but also further enhances the air stability and conductivity of sodium iron sulfate by introducing manganese ions and phosphate ions. As an efficient preparation method, spray drying technology can convert the precursor solution into uniform micron-sized particles in a short time, and form a stable positive electrode material structure through a subsequent sintering process. Compared with traditional preparation methods, spray drying has the significant advantages of simple process, low cost, and suitability for industrial production.

[0027] The purpose of the present invention is to provide an anion-cation co-doped sodium ferric sulfate positive electrode material, which greatly improves the conductivity and structural stability of the sodium ferric sulfate material, significantly improves the sodium storage electrochemical performance, and solves the problem of poor air stability of the material, providing technical support for the high performance and large-scale application of sodium ion batteries.

[0028] In order to achieve the above object, the first aspect of the present invention provides a method for preparing an anion-cation co-doped sodium iron sulfate positive electrode material, comprising the following steps:

[0029] Evenly disperse ferrous sulfate, manganese sulfate, sodium sulfate, sodium phosphate and conductive carbon material in water according to a certain proportion to obtain a mixed solution.

[0030] The mixed solution is spray-dried at a certain temperature to obtain precursor particles;

[0031] In an inert atmosphere, the precursor particles are heated to a predetermined temperature and kept warm for a period of time to obtain an anion-cation co-doped sodium iron sulfate positive electrode material.

[0032] The present invention is to prepare a precursor mixed solution by uniformly dispersing ferrous sulfate, manganese sulfate, sodium sulfate, sodium phosphate and conductive carbon material in water according to a certain proportion, and then quickly forming uniform particles by spray drying. Due to the addition of additional raw materials and the self-assembly properties of sodium ferric sulfate ions, other metal ions or anions can easily enter the corresponding ion sites of sodium ferric sulfate in the solution, and then the doped material undergoes phase transformation and crystallization during high-temperature sintering to obtain a sodium ferric sulfate material co-doped with anions and cations. Compared with the traditional method, the process greatly improves the structural stability and electronic conductivity of the sodium ferric sulfate cathode material, ensures the efficient transmission of sodium ions and electrons, and is suitable for industrial production. The prepared material has a high sodium storage capacity, a high voltage platform, excellent cycle stability and rate performance, and significantly enhances stability in a humid environment. The method uses low-cost, easily available raw materials, combined with an environmentally friendly and efficient process flow, and is widely used in fields such as grid energy storage and low-speed electric vehicles, providing reliable support for the commercialization of sodium ion batteries.

[0033] The molar ratio of ferrous sulfate to manganese sulfate is 1:0.1-0.5; the molar ratio of the total molar amount of manganese sulfate and ferrous sulfate to sodium sulfate is 1:1.5-2.0; and the molar ratio of sodium sulfate to sodium phosphate is 1:0.05-0.2.

[0034] The conductive carbon material is one or more of carbon nanotubes, graphene, Ketjen black, conductive graphite, and acetylene black.

[0035] The mass percentage of the conductive carbon material is 3-15%.

[0036] When the mixed solution is spray-dried at a certain temperature, the mixed solution is placed in a spray device. The temperature is 120-200°C and the spraying rate is 100-300m 3 / h.

[0037] The precursor particles are heated to a predetermined temperature and kept warm for a period of time, including: a heating rate of 0.5 to 20° C. / min, a predetermined temperature of 300 to 450° C., and a keeping time of 3 to 48 hours.

[0038] The inert atmosphere is one or more of argon, nitrogen, and helium.

[0039] A second aspect of the present invention provides an anion-cation co-doped sodium iron sulfate positive electrode material.

[0040] Preferably, Na 2.9 Fe 1.6 Mn 0.1 (SO4) 2.7 (PO4) 0.3 Cathode material;

[0041] Na 2.6 Fe 1.7 Mn 0.15 (SO4) 2.85 (PO4) 0.2 Cathode material;

[0042] Na 3.1 Fe 1.8 Mn 0.1 (SO4) 2.85 (PO4) 0.4 Positive electrode material.

[0043] A third aspect of the present invention provides an application of an anion-cation co-doped sodium iron sulfate positive electrode material in a sodium ion battery.

[0044] It should be noted that the experimental methods used in the present invention are all conventional methods unless otherwise specified; the reagents and materials used are all commercially available unless otherwise specified.

[0045] Example 1

[0046] Na 2.9 Fe 1.6 Mn 0.1 (SO4) 2.7 (PO4) 0.3 Preparation of positive electrode materials:

[0047] (1) 0.32 mol of ferrous sulfate, 0.02 mol of manganese sulfate, 0.2 mol of sodium sulfate, 0.06 mol of sodium phosphate, and 8 wt % of graphene were mixed, dissolved and dispersed in deionized water.

[0048] (2) The mixed solution was injected into the spray dryer, and the drying parameters were set to an operating temperature of 180°C and a spray rate of 200 m / s. 3 / h.

[0049] (3) The obtained dried product is placed in an argon protective atmosphere furnace for sintering, and the sintering process parameters are as follows: sintering temperature 350°C, heating rate 1°C / min, and holding time 6h. The final product is obtained when the temperature is cooled to room temperature.

[0050] Example 2

[0051] Na 2.6 Fe 1.7 Mn 0.15 (SO4) 2.85 (PO4) 0.2 Preparation of positive electrode materials:

[0052] (1) 0.17 mol of ferrous sulfate, 0.015 mol of manganese sulfate, 0.1 mol of sodium sulfate, 0.02 mol of sodium phosphate, and 5 wt % of carbon nanotubes were mixed, dissolved and dispersed in deionized water.

[0053] (2) The mixed solution was injected into the spray dryer, and the drying parameters were set to an operating temperature of 150°C and a spray rate of 180 m / s. 3 / h.

[0054] (3) The obtained dried product is placed in a nitrogen atmosphere furnace for sintering, and the sintering process parameters are as follows: sintering temperature 380°C, heating rate 3°C / min, and holding time 8h. The final product is obtained when the temperature is cooled to room temperature.

[0055] Example 3

[0056] Na 3.1 Fe 1.8 Mn 0.1 (SO4) 2.85 (PO4) 0.4 Preparation of positive electrode materials:

[0057] (1) 0.18 mol of ferrous sulfate, 0.01 mol of manganese sulfate, 0.1 mol of sodium sulfate, 0.04 mol of sodium phosphate, and 10 wt % of Ketjen black were mixed, dissolved and dispersed in deionized water.

[0058] (2) The mixed solution was injected into the spray dryer, and the drying parameters were set to an operating temperature of 200°C and a spray rate of 240 m / s. 3 / h.

[0059] (3) The obtained dried product is placed in an argon protective atmosphere furnace for sintering, and the sintering process parameters are as follows: sintering temperature 360°C, heating rate 5°C / min, and holding time 10h. The final product is obtained when the temperature is cooled to room temperature.

[0060] Comparative Example 1

[0061] Preparation of Na2Fe2(SO4)3 positive electrode material:

[0062] (1) 0.2 mol of ferrous sulfate, 0.1 mol of sodium sulfate and 10 wt% of Ketjen black were mixed, dissolved and dispersed in deionized water.

[0063] (2) The mixed solution was injected into the spray dryer, and the drying parameters were set to an operating temperature of 180°C and a spray rate of 200 m / s. 3 / h.

[0064] (3) The obtained dried product is placed in an argon protective atmosphere furnace for sintering, and the sintering process parameters are as follows: sintering temperature 350°C, heating rate 1°C / min, and holding time 6h. The final product is obtained when the temperature is cooled to room temperature.

[0065] In order to illustrate the relevant properties of the anion-cation co-doped sodium iron sulfate positive electrode material provided by the present invention, it is described in conjunction with the accompanying drawings.

[0066] Figure 1 This is the infrared spectrum of the positive electrode material prepared in Example 1. The peaks shown in the figure are typical absorption peaks of sulfate ions in the positive electrode material, indicating that the material is successfully prepared without destroying the crystal structure of sodium iron sulfate.

[0067] Figure 2 This is a Raman image of the positive electrode material prepared in Example 1. The peaks shown in the figure are the defects of the carbon material in the positive electrode material and the Raman peaks induced by graphite, indicating that the carbon material has been successfully composited with the positive electrode material.

[0068] In order to further illustrate the application of the anion-cation co-doped sodium iron sulfate positive electrode material prepared by the present invention in a sodium ion battery, the positive electrode material prepared in Example 1 is taken as an example to carry out sodium ion battery assembly and electrochemical performance testing:

[0069] The battery pole piece is prepared by dispersing and dissolving the anion and cation co-doped sodium iron sulfate positive electrode material prepared in Example 1 with conductive carbon black and polyvinylidene fluoride in a mass ratio of 8:1:1 in N-methylpyrrolidone, coating it on aluminum foil after uniform dispersion, and then drying it in a vacuum drying oven at 110°C for 12 hours to obtain the positive electrode pole piece. It is cut into discs with a diameter of 12 mm, and assembled into button cells using glass fiber as a separator, 1M NaClO4 ester-based electrolyte + 5% FEC as an electrolyte, and a metal sodium sheet as a counter electrode for subsequent electrochemical testing.

[0070] Figure 3 This is the cyclic voltammetry curve of the anion-cation co-doped sodium iron sulfate positive electrode material prepared in Example 1 at a scan rate of 0.2 mV / s. It can be seen that the material has a pair of obvious redox peaks and high electrochemical reversibility.

[0071] Figure 4 The charge and discharge curve of the anion-cation co-doped sodium iron sulfate positive electrode material prepared in Example 1 at a current density of 0.1 C. The reversible specific capacity of the material reaches 104 mAh / g, which is 25% higher than the 83 mAh / g of the control sample.

[0072] Figure 5The figure is a cycle performance diagram of the anion-cation co-doped sodium iron sulfate positive electrode material prepared in Example 1 at a current density of 1C. It has a reversible capacity of 73.6mAh / g at 1C, and no obvious attenuation is observed after 50 cycles, indicating that the material prepared by the present invention has excellent electrochemical properties and confirms the technical feasibility of the present invention.

[0073] Figure 6 This is the cycle performance diagram of the sodium iron sulfate positive electrode material prepared in Control Example 1 at a current density of 1C. Its reversible capacity at 1C is only 40.3mAh / g, which is Figure 5 There is a large gap in the capacity of anion-cation co-doped sodium ferric sulfate positive electrode materials, indicating that the technology of the present invention has an excellent effect on improving the sodium storage performance of sodium ferric sulfate positive electrode materials.

[0074] The present invention describes preferred embodiments and their effects. However, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0075] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing an anion-cation co-doped sodium iron sulfate positive electrode material, characterized in that: The following steps are involved: Evenly disperse ferrous sulfate, manganese sulfate, sodium sulfate, sodium phosphate and conductive carbon material in water according to a certain proportion to obtain a mixed solution. The mixed solution is spray-dried at a certain temperature to obtain precursor particles; In an inert atmosphere, the precursor particles are heated to a predetermined temperature and kept warm for a period of time to obtain an anion-cation co-doped sodium iron sulfate positive electrode material.

2. The method for preparing anion-cation co-doped sodium iron sulfate positive electrode material according to claim 1, characterized in that: The molar ratio of the ferrous sulfate to manganese sulfate is 1:0.1-0.5; the molar ratio of the total molar amount of manganese sulfate and ferrous sulfate to sodium sulfate is 1:1.5-2.0; and the molar ratio of sodium sulfate to sodium phosphate is 1:0.05-0.

2.

3. The method for preparing anion-cation co-doped sodium iron sulfate positive electrode material according to claim 1, characterized in that: The conductive carbon material is one or more of carbon nanotubes, graphene, Ketjen black, conductive graphite, and acetylene black.

4. The method for preparing anion-cation co-doped sodium iron sulfate positive electrode material according to claim 3, characterized in that: The mass percentage of the conductive carbon material is 3-15%.

5. The method for preparing anion-cation co-doped sodium iron sulfate positive electrode material according to claim 1, characterized in that: When the mixed solution is spray-dried at a certain temperature, the mixed solution is placed in a spray device. The temperature is 120-200°C and the spraying rate is 100-300m 3 / h.

6. The method for preparing anion-cation co-doped sodium iron sulfate positive electrode material according to claim 1, characterized in that: The precursor particles are heated to a predetermined temperature and kept warm for a period of time, including: a heating rate of 0.5 to 20° C. / min, a predetermined temperature of 300 to 450° C., and a holding time of 3 to 48 hours.

7. The method for preparing anion-cation co-doped sodium iron sulfate positive electrode material according to claim 1, characterized in that: The inert atmosphere is one or more of argon, nitrogen, and helium.

8. An anion-cation co-doped sodium iron sulfate positive electrode material prepared by the method according to any one of claims 1 to 7.

9. Use of the anion-cation co-doped sodium iron sulfate positive electrode material according to claim 8 in a sodium ion battery.

Citation Information

Patent Citations

  • Sodium-ion battery positive electrode material, preparation method thereof and sodium-ion battery

    CN115050957A

  • Preparation method of sodium ion battery positive electrode material

    CN115385380A

  • Composite sodium ferrous sulfate positive electrode material as well as preparation method and application thereof

    CN116995227A

  • Sodium ferric sulfate positive electrode material and preparation method and application thereof

    CN118651895A

  • Micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material and sodium ion battery or sodium battery prepared from same

    WO2023087485A1

Cited By

  • Modified sodium ferric sulfate positive electrode material as well as preparation method and application thereof

    CN121449109A